Ketidakpastian Komunikasi Santri Shigar Di Pondok Modern Darussalam Gontor - Rukmini, Diah; Harahap, Fariz Istiqlal (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
The study aims to determine and analyze the communication uncertainty experienced by new students (sighar) at the Darussalam Gontor Modern Islamic Boarding School. The theory used in this study is the uncertainty reduction theory pioneered by Charles Berger and Richard Calabrese, using a qualitative case study design method. The theory used in this study is the uncertainty reduction theory pioneered by Charles Berger and Richard Calabrese. The method used in this study is a qualitative method with a case study design. Data collection techniques were carried out through interviews with 7 informants using purposive sampling. This study produced information that new shigar students in the Al-Azhar building experienced communication uncertainty, which they experienced was cognitive uncertainty such as imagining violence in the boarding school, imagining difficult boarding school lessons, differences between teachers in the boarding school and teachers outside. In addition, the students experienced behavioral uncertainty, thinking that all friends in the boarding school would be kind and caring, thinking that in the boarding school they were free to use Indonesian, and having difficulty adapting to the discipline of the boarding school. To reduce communication uncertainty, sighar students used strategies, namely passive, active, and interactive strategies. Passive strategies are carried out by observing friendly friends, observing friends who are not emotional, observing homeroom teachers and teachers in the class. Active strategies are used by searching for information on Islamic boarding schools in BIMAGO, asking for information on Islamic boarding schools to ustadz in PRIMAGO, asking for solutions to each problem to administrators and teachers. Interactive strategies are used by consulting with ustadz consulate telling stories with friends in the consulate.